Association between changes in renal function and clinical outcomes in anticoagulated atrial fibrillation patients with marginal renal function. A nationwide observational cohort study - Lee, Kyung-Yeon; Lee, So-Ryoung; Choi, Eue-Keun; Choi, JungMin; Ahn, Hyo-Jeong; Kwon, Soonil; Kim, Bongseong; Han, Kyung-Do; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2024)
Background Renal function is one of the crucial components for determining the dose and type of oral anticoagulants in atrial fibrillation (AF) patients, and is also closely associated with the risks of stroke and bleeding. This study aimed to assess renal function changes and their impact on clinical outcomes in anticoagulated AF patients with marginal renal function. Methods From a Korean claims database, patients with AF on anticoagulants and a baseline eGFR of 45 to <60 ml/min/1.73 m2 were studied. Patients were grouped by changes in renal function over two years—maintained, improved (eGFR >60 ml/min/1.73 m2), or worsened (eGFR <45 ml/min/1.73 m2)—the study analyzed outcomes including ischemic stroke, major bleeding, end-stage renal disease (ESRD), all-cause death, and a composite of clinical outcomes. Results A total of 5,126 patients were included in the study: 2,170 (42.3%) in the maintained group, 2,276 (44.4%) in the improved group, and 680 (13.1%) in the group with worsened renal function. The worsened group was older and had more prevalent comorbidities than other groups. After multivariable adjustment, the worsened group was associated with significantly higher risks of major bleeding (adjusted hazard ratio, 95% confidence interval; 1.46, 1.03–2.07, p = 0.035), ESRD (1.49, 1.24–1.80, p < 0.001), all-cause death (9.29, 4.92–17.6, p < 0.001), and the composite outcome (1.57, 1.36–1.83, p < 0.001). Conclusions In anticoagulated AF patients with marginal renal function, a substantial proportion of patients experienced renal function decline below eGFR 45 ml/min/1.73 m2 within 2 years. Renal function decline was associated with higher risks of major bleeding, ESRD, all-cause death, and the composite outcome compared to those who maintained their baseline renal function.